Krivičnopravni značaj afektivnih stanja - Nataša Delić (Revija za kriminologiju i krivično pravo)
The first part of this paper briefly explains the psychological nature of emotions and affective conditions. The second part of the paper deals with emotions in the general and the special part of the criminal law. In the context of motives out of which a crime is committed, emotions can have significance in sentencing. Special attention is dedicated to „base motives“, feelings of hatred and compassion, and to their significance in criminal law. The u7second, lengthier part of the paper is concerned with affective conditions in criminal law. The theoretical analysis of this matter encompasses the view on affective conditions as possible causes of a temporary mental disorder, which is a biological basis of unaccountability/significantly diminished accountability (art. 23 CC) and the legal concepts of the „heat of passion“ and „fright“ that generally correspond to the feeling of anger or the feeling of fear. This is connected to the legal concept of exceeding the limits of lawful defense (art. 19 par. 3 CC), as well as to the criminal offences of murder in a heat of passion (art. 115 CC) and severe bodily injury in a heat of passion (art. 121 par. 5 CC). Other criminal offences also include the affective conditions of the passive subject as a basic or supplemental element. The final, third part of the paper contains conclusions backed up with relevant arguments.